ANALISIS KUALITAS JARINGAN WIFI.ID PADA KOPI JANJI JIWA CIJERAH BERDASARKAN PARAMETER QOS (QUALITY OF SERVICE) - Disastra, Andika Dwipraja; Hidayat, M. Reza (Jurnal Teknik, 2024)
One of the services provided by Kopi Janji Jiwa Cijerah is the internet, therefore research is conducted aimed at testing and improving the quality of the internet network WiFi.ID at the Kopi Janji Jiwa Cijerah place based on Quality of Service (QoS) parameters with the Drive Test method. The test was conducted by The Drive method using Wireshark software for ± 6 hours within 7 days at 12.00-18.00 WIB at Kopi Janji Jiwa Cijerah by utilizing the services provided on the spot that is WiFi.ID where the first test at access point 2,4 GHz type TP-LINK CPE205 2,4 GHz then the second test after optimization using Access Point 5 GHz tent type 06 P2P 5 GHz. Quality of Service (QoS) parameters tested and analyzed consist of delay, throughput, jitter and packet loss with tiphon standards that are the reference classification. The results in the first test resulted in an index of average QoS parameters based on the TIPHON standard of 3.575 and in the second test that after optimization got an average value index from the QoS parameter based on the TIPHON standard of 3,925, based on the value index there was an improvement in the quality of the network, then the quality of the internet network WiFi.ID in Kopi Janji Jiwa Cijerah got a Good classification and approached Very Good.